CULTURAL BELIEFS AND SPIRITUAL WELLBEING AMONG WOMEN EXPERIENCING RELIGIOUS TRANCE - Blessy, Valsarj Prabha; Savitha (Journal of Health and Allied Sciences NU, 2013)
Background: Every culture has unique ways of beliefs and practices with regard to religion and spirituality. Many rituals like possession, religious trance that are prevalent in society are considered normal especially when performed in a close community or group. Spirit possession is a culturally sanctioned, heavily institutionalized and symbolically invested means of expression in action for various ego dystonic impulses and thoughts.1Aim: was to assess the cultural beliefs and spiritual wellbeing among women experiencing religious trance.Methods: A descriptive correlative survey design was used. Thirty one women who had experienced religious trance on the day of 'Siri jaatre' (Annual festival held in the temple) at Sree Veerabhadra Swamy temple, Hiriadka were selected for the study using purposive sampling technique. The instruments used for the study were Demographic Proforma, Cultural Belief Scale and Spiritual Wellbeing Questionnaire. Descriptive and inferential statistics were used for analysis of the data.Results: Majority women were illiterate (67.7%), coolie workers (61.3%) and married (93.5%). All the women (100%) had high cultural beliefs and high spiritual wellbeing. There was high correlation (r=0.624) between cultural beliefs and spiritual wellbeing.
Keywords: Religious trance; women; spiritual wellbeing; cultural belief